Opening reionization: quantitative morphology of the epoch of reionization and its connection to the cosmic density field. Issue 3 (27th August 2020) - Busch, Philipp; Eide, Marius B; Ciardi, Benedetta; Kakiichi, Koki
ABSTRACT: We introduce a versatile and spatially resolved morphological characterization of binary fields, rooted in the opening transform of mathematical morphology. We subsequently apply it to the thresholded ionization field in simulations of cosmic reionization and study the morphology of ionized regions. We find that an ionized volume element typically resides in an ionized region with radius ∼8  h −1  cMpc at the midpoint of reionization ( z ≈ 7.5) and follow the bubble size distribution even beyond the overlap phase. We find that percolation of the fully ionized component sets in when 25 per cent of the universe is ionized and that the resulting infinite cluster incorporates all ionized regions above ∼8  h −1  cMpc. We also quantify the clustering of ionized regions of varying radius with respect to matter and on small scales detect the formation of superbubbles in the overlap phase. On large scales, we quantify the bias values of the centres of ionized and neutral regions of different sizes and not only show that the largest ones at the high-point of reionization can reach b ≈ 30, but also that early small ionized regions are positively correlated with matter and large neutral regions and late small ionized regions are heavily antibiased with respect to matter, down to b ≲ −20.